The impact of photopigment bleaching on the human rod photoreceptor subretinal space measured via optical coherence tomography - Messner, Alina (2024)
PURPOSE. The purpose of this study was to investigate rod photopigment bleaching-driven intrinsic optical signals (IOS) in the human outer retina and its measurement repeatability based on a commercial optical coherence tomography (OCT) platform. METHODS. The optical path length of the rod photoreceptor subretinal space (SRS), that is, the distance between signal bands of rod outer segment tips and retinal pigment epithelium, was measured in 15 healthy subjects in ambient light and during a long-duration bleaching white-light exposure. RESULTS. On 2 identical study days (day 1 and day 2 [D1 and D2]), light stimulation resulted in a significant decrease in rod SRS by 21.3 ± 7.6% and 19.8 ± 8.5% (both P < 0.001), respectively. The test-retest reliability of the SRS maximum change of an individual subject was moderate for single measures (intraclass correlation coefficient [ICC] = 0.730, 95% confidence interval [CI] = 0.376, 0.900, P < 0.001) and good for average measures (ICC = 0.844, 95% CI = 0.546, 0.947, P < 0.001). The mean area under the stimulus response curve with values of 14.8 ± 9.4 and 15.5 ± 7.5 μm × minutes (P = 0.782) showed excellent agreement between the stimulus response on D1 and D2. Intermittent dark adaptation of the retina led to an initial increase of the SRS by 6.1% (P = 0.018) and thereafter showed a decrease toward baseline, despite continued dark adaptation. CONCLUSIONS. The data indicate the potential of commercial OCT in measuring slow IOS in the outer retina suggesting that the rod SRS could serve as a biomarker for photoreceptor function. The presented approach could provide an easily implementable clinical tool for the early detection of diseases affecting photoreceptor health.